How to Support Student Learning? (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The article states my learning and teaching experience during the Student Support learning (SSL) module at Westminster University in Tashkent (WIUT). You can dive into insights that completely changed my mind towards teaching. I have been exploring a teaching and learning journey with euphoria and enthusiasm. I believe that you also can feel this journey’s discoveries on the way with me by reading this article. In this article you can read about ‘A-ha! Moments’ during the module, my applications of insights that I have stated below and self-reflection on my own teaching.